Impact of marketing strategy of GlaxoSmithKline Bangladesh Ltd. - Sharifat, Umma Hafiza Sharifatun Nesa (BRAC University, 2017)
This internship report is submitted in a partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2016.